La eficacia de rol, la claridad de rol y el rendimiento en jóvenes futbolistas - Fabra López, Priscila; Castillo Fernández, Isabel María; Ródenas Cuenca, Luis Tomás; Mercé Cervera, Juan; R. Bray, Steven; Balaguer Solá, Isabel (Universitat de les Illes Balears Universitat Autònoma de Barcelona, 2014)
The aim of this study was twofold: 1) to analyze the relationship between role efficacy, role clarity, and role performance effectiveness as a subjective measure of performance, and 2) to examine role clarity as a moderator of the role efficacy-performance relationship, in both an offensive and defensive context in football. Two hundred and ninety-five male soccer players between 12 and 16 years old (M = 14.01, SD = 1.09) completed the questionnaires assessing the variables of the study. Results showed that the players who reported higher role clarity also reported higher role efficacy and performed better than those with lower role clarity. Also, role clarity was a moderator for defensive role functions; specifically, role efficacy was a positive predictor of performance only when role clarity was high.